The decisive role of magnetic anisotropy in honeycomb layered Li3Ni2SbO6 and Na3Ni2SbO6 - Werner, Johannes; Hergett, Waldemar; Park, Jaena; Koo, Changhyun; Klingeler, Rüdiger (Journal of magnetism and magnetic materials, 2019)
The decisive role of magnetic anisotropy even in systems with small anisotropy is illustrated for the honeycomb-layered antiferromagnets A3Ni2SbO6 with A=Li and Na. Both systems evolve long range magnetic order below TN=14 and 16.5K, respectively. The magnetic phase diagrams obtained from static magnetisation studies up to 15T imply competing antiferromagnetic phases and a tricritical point at TN. The phase boundaries are visible in the dynamic response of the antiferromagnetic resonance modes, too, which investigation by means of high frequency/high field electron spin resonance enables precise determination of magnetic anisotropy. The anisotropy gap amounts to Δ=360±2GHz in Na3Ni2SbO6 while in Li3Ni2SbO6 orthorhombicity is associated with Δ=198±4 and 218±4GHz. Above TN, the data imply short-range antiferromagnetic order up to at least 80K. The data suggest a crucial role of anisotropy for selecting the actual spin structure at B=0T.
Gesehen am 04.04.2019
Im Titel sind die Zahlen "3", "2" und "6" tiefgestellt